Review of external neck landmarks in the aspect of operative surgical care - K. A. Zhandarov; S. S. Dydykin; A. V. Mirontsev; I. P. Polovikov; G. A. Garaeva (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
Background. The high prevalence of neck injuries and the complexity of their surgical treatment represent one of the key challenges in modern clinical anatomy and operative surgery. Understanding the external anatomy of the neck plays a critical  role in the diagnosis and treatment of these injuries.Objective. To systematize and analyze data on external neck landmarks, their classification, and significance in surgical practice, with a particular emphasis on applications in operative and military field surgery.Methods. A comprehensive analysis of historical and contemporary scientific sources on neck anatomy and surgery was conducted. Works ranging from ancient authors (Hippocrates, Vesalius, Leonardo da Vinci) to modern researchers were examined, including studies by domestic scientists (A.P. Samarin, V.N. Shevkunenko,  S.N.  Delitsyn) and foreign specialists (Monson). Results. A classification of external neck landmarks is presented, dividing them into primary (bone and muscle structures, such as the sternocleidomastoid muscle, jugular notch of  the  sternum,  laryngeal  cartilages)  and  secondary  (superficial  vessels  and nerves). Their application in determining anatomical boundaries, localizing wound channels, and performing surgical interventions is described. The importance of knowledge of these landmarks for external examination, diagnosis, patient triage, and provision of primary and specialized medical care is emphasized.Conclusions. Knowledge of external neck landmarks is fundamental for the effective performance of surgical manipulations and improving treatment outcomes for patients with neck injuries. This research has particular practical significance for military field surgery, where rapid and accurate diagnosis and treatment of neck wounds can be  critical for saving  patients' lives.Practical  Significance. The results of the study can be used to improve diagnostic and treatment methods for neck injuries, as well as for training surgeons.